Kajian Pragmatis Transformasi Manajemen Waktu Pendidikan Sekolah 5 hari di Kota Pematangsiantar - Bismar Sibuea; Mardin Silalahi; Tiodora Sillahi; Anita Purba (Attractive : Innovative Education Journal, 2026)
The transformation of learning time management through the five-day school policy has become an important discourse in the Indonesian education system. This policy aims to improve learning effectiveness and provide broader opportunities for students’ character development. However, the implementation of such policy requires a comprehensive study that considers the readiness of various stakeholders and the socio-economic conditions of the community. This study aims to analyze the dynamics of the five-day school policy discourse in Pematangsiantar City and to identify factors influencing the readiness of schools, teachers, students, and parents in responding to changes in the learning time system. This research employs a qualitative approach using descriptive analysis of educational data, socio-economic conditions of the community, and stakeholder responses toward the policy. The findings indicate that the implementation of the five-day school system in Pematangsiantar has not been evenly adopted because the policy is not mandatory for all educational institutions. Furthermore, teacher readiness, socio-economic conditions of students’ families, transportation accessibility, and school infrastructure readiness are significant factors affecting the effectiveness of policy implementation. The study also reveals that changes in the learning time system potentially generate multidimensional impacts on educational, social, and economic aspects of society. Therefore, a more comprehensive policy analysis using a transdisciplinary approach is required before implementing the policy more broadly.